Securing peer-to-peer mobile communications using public key cryptography: new security strategy - Al- Bakri, S.H.; Mat Kiah, M.L.; Zaidan , A. A.; Zaidan, B.B.; Alam, Gazi Mahabubul (Academic Journals, 2011)
Mobile phones are considered to be the most common communication devices in history. Recently, mobile phones are not only used for casual greetings but also, sending and receiving important data such as, social security numbers, bank account details and passwords. Public key cryptography is a proven security solution, which can be used to secure the mobile communications. Several researchers have proposed server-based architectures public key cryptography solution to secure the mobile communications. Third party servers were used to check the certificates, authenticating the communicating parties, key distribution, etc. This paper proposes and implements a non-server (that is, P2P), architecture public key cryptography to secure the mobile communications. The proposed implementation of public key cryptography can provide confidentiality, authentication, integrity and non-repudiation security services needed for mobile communication. Compared with server based architecture, non-server based architecture has lower risk and the security has been improved, to avoid many kinds of attacks.